Domestication of Pea (Pisum sativum L.): The Case of the Abyssinian Pea - Weeden, Norman F. (Frontiers in Plant Science, 2018)
Phylogenetic relationships of the Abyssinian pea (Pisum sativum ssp. abyssinicum) to other subspecies and species in the genus were investigated to test between different hypotheses regarding its origin and domestication. An extensive sample of the Pisum sativum ssp. sativum germplasm was investigated, including groups a-1, a-2, b, c, and d as identified by Kwon et al., 2012). A broad sample of P. fulvum but relatively few P. s. ssp. elatius accessions were analyzed. Partial sequences of 18 genes were compared and these results combined with comparisons of additional genes done by others and available in the literature. In total, 54 genes or gene fragment sequences were involved in the study. The observed affinities between alleles in P. ssp. sativum, P. s. ssp. abyssinicum, P. s. ssp. elatius, and P. fulvum clearly demonstrated a close relationship among the three P. sativum subspecies and rejected the hypothesis that the Abyssinian pea was formed by hybridization between one of the P. sativum subspecies and P. fulvum. If hybridization were involved in the generation of the Abyssinian pea, it must have been between P. s. ssp. sativum and P. s. ssp. elatius, although the Abyssinian pea possesses a considerable number of highly unique alleles, implying that the actual P. s. ssp. elatius germplasm involved in such a hybridization has yet to be tested or that the hybridization occurred much longer ago than the postulated 4000 years bp. Analysis of the P. s. ssp. abyssinicum alleles in genomic regions thought to contain genes critical for domestication indicated that the indehiscent pod trait was independently developed in the Abyssinian pea, whereas the loss of seed dormancy was either derived from P. s. ssp sativum or at least partially developed before the P. s. ssp. abyssinicum lineage diverged from that leading to P. s. ssp. sativum.